Additions to the saprobic fungi (Ascomycota) associated with macadamia trees from the Greater Mekong Subregion - Xian Zhang; Saowaluck Tibpromma; Samantha C. Karunarathna; Tian-Ye Du; Li-Su Han; Abdallah M. Elgorban; Jaturong Kumla; Chanokned Senwanna; Dong-Qin Dai; Nakarin Suwannarach; Hao-Han Wang (MycoKeys)
Macadamia trees, the most economically important Proteaceae perennial crop, are globally renowned for their edible nuts. During our surveys of microfungi associated with macadamia in China and Thailand, we isolated three saprobic fungi from dead macadamia branches. Our multigene phylogenetic analyses (ITS, LSU, SSU, tef1-α, TUB2, and ACT loci), genealogical concordance phylogenetic species recognition (GCPSR) with a pairwise homoplasy index (PHI) test, and morphological characteristics led to the discovery of two new species, Dothiorella macadamiae and Phaeoacremonium chiangmaiense, and one new record, Melomastia puerensis. We provide morphological descriptions, photo plates, phylogenetic analysis results, and PHI test results of the two new species, along with comparisons with closely related taxa. These findings have global implications for understanding the diversity of microfungi associated with macadamia trees.